Daily consumption of caper fruit along with atorvastatin has synergistic effects in hyperlipidemic patients: Randomized clinical trial: - Esmaeili, Seied Saeid; Sardari, Saeed; Fallahi, Faramarz; Davati, Ali; Emadi, Fatemeh; Gholamifesharaki, Mohammad; Khavasi, Narjes (Galen Medical Journal, 2019)
Background: Dyslipidemia leads to micro- and macro-vascular complications. Atorvastatin is the main therapeutic drug used for dyslipidemia, but it causes side effects such as new type 2 diabetes mellitus onset and elevation of liver enzymes. Herbs may be useful in reducing atorvastatin doses. Caper fruit, an herbal drug in Iranian traditional medicine, has hypolipidemic effects. Hence, the effect of atorvastatin therapy with and without daily caper fruit pickle (CFP) consumption was assessed on hyperlipidemia. Materials and Methods: In this single-blinded, randomized, controlled trial, 60 hyperlipidemic patients were allocated in two groups and treated with 10â€…mg atorvastatin plus 40-50 g CFP (A10+CFP) or atorvastatin alone (A10) for eight weeks. Biochemical parameters were measured at baseline, 4, and eight weeks of the intervention. One-way repeated measure ANOVA and mixed ANOVA were used to measure the effect of the two treatments and the interaction between the type of treatment and time on lipid profile. Results: Serum total cholesterol and low-density lipoprotein cholesterol (LDL-C) were significantly decreased in the A10+CFP group compared with the A10 group (P<0.001 and P<0.001, respectively) from baseline up to the week 8. At week 4, mean changes of LDL-C was significantly higher in the A10+CFP compared with the A10 (P=.01). Adjusting for the baseline variables, the mean difference of alanine aminotransferase (P<0.01) and triglyceride (P=.003) were significantly higher in the A10+CFP group at the end. Conclusion: This study reports that the intake of CFP along with atorvastatin daily may have synergistic effects which improve the lipid profile in hyperlipidemic patients.Â [GMJ.2019;8:e1345]